Cultivation of avian reovirus ARV04/02 strain in different cell cultures - M. N. Mitrofanova; L. V. Malakhova; B. L. Manin (Ветеринария сегодня)
The paper demonstrates data on experimental cultivation of avian reovirus tenosynovitis agent in different cell cultures. It was indicated that strain ARV04/02 was capable of reproduction in all tested cell cultures (CEF, Vero-V, PSKG-30, Taurus-4, MARC-145) at the first passage already. The highest level of the virus accumulation was observed in CEF culture at the infection dose of 0.1 TCID50/cell and during 72-96 hours of cultivation.